On the structure of C^*-algebra generated by a family of partial isometries and multipliers - Kuznetsova, A. Yu.; Patrin, Ye. V. (Armenian Journal of Mathematics, 2015)
In the paper we consider an operator algebra generated by a family of partial isometries associated with a self-mapping on a countable set and by multipliers. An action of the unit circle on this algebra is specified that determines its Z-grading. Under some conditions on the mapping the algebra is isomorphic to the crossed product of its fixed point subalgebra and the semigroup N.